2010
DOI: 10.1007/s00595-008-4027-9
|View full text |Cite
|
Sign up to set email alerts
|

Complications in primary and completed thyroidectomy

Abstract: There is no significant difference in complications between a primary TT and ST. The rates of complications after a completed thyroidectomy are significantly higher in comparison with the primary operations. High rates of reoperation in cases of recurrent pathology and incidental carcinoma were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 13 publications
2
47
2
1
Order By: Relevance
“…In our study, we found the complication rates in completion thyroidectomy for temporary and permanent hypoparathyroidism as 20.7% and 4.4% respectively where it is 2.5% for permanent RLN palsy and 8.1% in unilateral, 1.2% in bilateral temporary RLN palsy. For one thing, completion thyroidectomy after hemithyroidectomy reveals some differences (Vaiman et al, 2010). Complications generally occure while dissecting the scar tissue around recurrent laryngeal nerve or the vascular pedicle of the parathyroid glands.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found the complication rates in completion thyroidectomy for temporary and permanent hypoparathyroidism as 20.7% and 4.4% respectively where it is 2.5% for permanent RLN palsy and 8.1% in unilateral, 1.2% in bilateral temporary RLN palsy. For one thing, completion thyroidectomy after hemithyroidectomy reveals some differences (Vaiman et al, 2010). Complications generally occure while dissecting the scar tissue around recurrent laryngeal nerve or the vascular pedicle of the parathyroid glands.…”
Section: Discussionmentioning
confidence: 99%
“…Large case series suggest that rates of these complications are: haematoma, 1·2–2·1 per cent1, 2, 3, 4; transient hypoparathyroidism, 6·4–35·2 per cent1, 2, 4, 5, 6; permanent hypoparathyroidism, 0·9–6·3 per cent1, 2, 3, 5, 6; transient RLN injury, 0·36–3·9 per cent1, 2, 3, 4, 5; and permanent RLN injury, 0·7–1·4 per cent1, 2, 3, 5. Short‐term complications increase length of stay in hospital, the number of consultations, diagnostic tests and treatments needed, and overall cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is generally accepted that reoperation carries a higher risk of complications than primary surgery [5][6][7][8]. In addition, completion thyroidectomy requires working in a recently operated field with scarring and partial obliteration of tissue planes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases in which a thyroid lobectomy is performed and the final pathology is reported as regional lymph node metastasis, consideration is then given for a completion thyroidectomy. The rates of complications after completion thyroidectomy are significantly higher in comparison with the primary operation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%